2012
DOI: 10.1039/c2cp41881a
|View full text |Cite
|
Sign up to set email alerts
|

The impact of upper cut-off voltages on the electrochemical behaviors of composite electrode 0.3Li2MnO3·0.7LiMn1/3Ni1/3Co1/3O2

Abstract: This work has initiated an investigation on the electrochemical behaviors and the structure changes of the composite electrode 0.3Li(2)MnO(3)·0.7LiMn(1/3)Ni(1/3)Co(1/3)O(2) when charged with different cut-off voltages. It is found that the charge cut-off voltages could not only affect the capacity property and coulombic efficiency, but also alter the electrode kinetics of the composite. As a consequence, the electrochemical activation of the composite electrode is highly dependent on the charge cut-off voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 43 publications
1
27
1
Order By: Relevance
“…As clearly illustrated in Fig. 44 Another possible reason was that the irreversible loss of oxygen resulting from activation of the Li 2 MnO 3 component would retain a large number of tiny pores throughout the whole CL particles, which was conductive to HF attack on the inner of the spherical particles. The continuous increase of the stable tetravalent Mn could protect the cathode from etching by the generated HF in the electrolyte, suppress degradation of the cathode structure, and thus improve the long-term cycling stability of the cathode.…”
Section: Resultsmentioning
confidence: 99%
“…As clearly illustrated in Fig. 44 Another possible reason was that the irreversible loss of oxygen resulting from activation of the Li 2 MnO 3 component would retain a large number of tiny pores throughout the whole CL particles, which was conductive to HF attack on the inner of the spherical particles. The continuous increase of the stable tetravalent Mn could protect the cathode from etching by the generated HF in the electrolyte, suppress degradation of the cathode structure, and thus improve the long-term cycling stability of the cathode.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that a stepwise increase of potential limits increases subsequent discharge capacity for Li-rich electrodes. 12,[65][66][67][68][69] We believe both activation at low temperatures as well as the stepwise potential activation cause a slower activation of the material, resulting in a surface reorganization and a modified electrode/solution interface that improve the materials' capacity.…”
Section: Stabilization Of Voltage and Capacity Fadementioning
confidence: 99%
“…The major peaks of the diffraction patterns from the pristine electrode could be indexed to the standard layered a-NaFeO 2 structure (R3m) [25]. Superstructure peaks located at 20°-22° [26,27] [19,23,25]. Meanwhile, all the diffraction peaks progressively decrease with the upper charge cutoff potential (Fig.…”
Section: Xrd Analysis Of Electrode During the First Cyclementioning
confidence: 97%
“…Surendra et al [18] studied the surface reactions and changes in Li 1.2 Mn 0.525 Ni 0.175 Co 0.1 O 2 during different cycle potential windows. Yu et al [19] discovered that the reversible capacity of 0.3Li 2 MnO 3 Á0.7LiMn 1/3 Ni 1/3 Co 1/3 O 2 is highly dependent on the charge cutoff potentials. Watanabe et al [20] pointed out that the repeated charge/discharge cycles with a stepwise charge cutoff potential can improve the cycle performance of Li …”
Section: Introductionmentioning
confidence: 99%